Steps to improve umbilical vein catheterization in neonatal care - Marta Torres del Pino; Elisabet Gómez Santos; María Luisa Domínguez Quintero; Beatriz Mendoza Murillo; José Antonio Millán Zamorano; Gloria Toledo Muñoz-Cobo; David Mora Navarrocor (Elsevier, 2023)
Introduction: In neonatal units, umbilical vessel catheterization is the preferred method to gain vascular access in the initial management of the newborn because it is quick and easy.The failure rate ranges from to 50%, as the catheter can be found in the portal system in up to 40% of cases, leading to complications. This failure rate warrants the investigation of different methods to reduce the frequency of catheter malposition. We describe different techniques to improve the success rate in umbilical vein catheterization, such as the double catheter technique, positioning the newborn in right lateral decubitus for insertion, liver compression, and ultrasound-guided catheter insertion. The primary objective of the study was to assess the impact of new techniques on the success rate of central umbilical venous catheterization. Material and methods: Pre- and post-intervention quasi-experimental study in a level B NICU conducted in January-June 2022 (pre-intervention) and July-December 2022 (post-intervention). Results: Prior to the introduction of these new catheterization techniques, the failure rate of blind umbilical catheter insertion was 52%. Since the introduction of these measures, the overall failure rate has decreased to 27%. Conclusions: After the introduction of the new catheterization and recanalization methods, our success rate in umbilical vein catheterization has increased, and we believe it is necessary to implement them in units with similar failure rates to ours. Resumen: Introducción: En las unidades neonatales se utiliza el catéter venoso umbilical como acceso vascular de elección en la atención inicial del recién nacido debido a su rápido y fácil acceso. Presenta una tasa de fracaso del 25% al ​​50%, ya que hasta en un 40% de los casos puede encontrarse en el sistema portal conllevando complicaciones. Esto justifica la búsqueda de métodos para disminuir la tasa de catéteres mal posicionados. Se describen diferentes técnicas para mejorar la tasa de éxito a la hora de canalizar la vena umbilical, como son la técnica del doble catéter, la posición del recién nacido para canalizar en decúbito lateral derecho, la compresión hepática y la canalización de forma ecoguiada. El objetivo principal de este estudio es evaluar el impacto de las nuevas técnicas en la tasa de éxito de canalización venosa umbilical central. Material y métodos: Estudio cuasi-experimental pre y post intervención en una UCIN nivel B durante Enero-Junio 2022 (preintervención) y Julio-Diciembre 2022 (postintervención). Resultados: Previo a la introducción de estas nuevas técnicas de canalización nuestra tasa de fracaso en la canalización, siempre llevada a cabo a ciegas, era de un 52% y con la introducción de estas medidas ha disminuido la tasa de fracaso a un 27% de forma global. Conclusiones: Tras la introducción de los nuevos métodos de canalización y recanalización, nuestra tasa de éxito en la canalización de la vena umbilical ha aumentado, y creemos necesario implantarlo en unidades con tasas de fracaso similares a la nuestra.